developmental status of 5 year old very low birthweight children - sharafi, reza; hassanzadeh rad, afagh; akrami, narges; aminzadeh, vahid (Iranian Journal of Child Neurology, 2021)
Abstract Objective Some previous reports mentioned the improved survival with no disability in very low birthweight neonates (VLBW), However, 16% of these neonates encountered with the developmental disorders. Regarding the lack of previous investigations on the developmental status of 5 year old very low birthweight children, and according to the importance of early detection and treatment, we aimed to assess the developmental status of 5 year old very low birthweight children Materials & Methods This is a historical cohort study which was conducted on 5 year old children. Participants were divided into VLBW and normal birth weight groups (NBW). Data were gathered buy the ASQ questionnaire. This questionnaire consisted of 5 developmental domains including communication, gross motor, fine motor, problem solving, and personal-social skills. Data were reported by descriptive statistics including mean, standard deviation, number and percent and analyzed by Mann Whitney U test, and independent T test in SPSS v 22. Results A total of 106 five-year-old children, including two groups of VLBW and NBW, participated in this study. The results of Mann-Whitney U test showed a significant difference between the groups regarding the scores of communication (P=0.002), gross motor (P<0.001), fine motor (P<0.001), and problem-solving (P<0.001) skills. However, no significant difference was found between the groups regarding the personal/social developmental status (P=0.559). Conclusion According to the results, higher risk of developmental delay was observed in VLBW infants compared to normal weight neonates, therefore, it is recommended to perform developmental screening tests for on time detection of high risk children and performing early diagnostic and therapeutic interventions.